A framework for ranking potential cities for implementing emerging urban mobility technologies: A case study for eVTOL aircraft - Felix Spühler; Kristian Siebenrock; Ivan Terekhov; Dirk C. Mattfeld (Journal of Urban Mobility)
Urban mobility is an important component of a well-functioning city. Moreover, it is an important sector that must be considered in the steady transition of cities. During this transition, new opportunities for mobility technologies are constantly emerging, as, for example, electric Vertical Take-Off and Landing (eVTOL) aircraft. However, due to various factors, not every new mobility technology is suitable for every city. Finding suitable cities for implementing such a technology is therefore a crucial task. In our research, we address the problem of evaluating and ranking potential cities in terms of their suitability for the deployment of a particular emerging mobility technology. For this, we introduce an index and a framework for evaluating and ranking these cities. In this framework, we apply the novel Urban Mobility Innovation Adaption (UMIA) index and the well-known Analytical Hierarchy Process (AHP) to evaluate and rank each city regarding a chosen mobility technology. In our case study, we evaluate and rank cities on deploying eVTOL aircraft. Our results indicate the effectiveness and validity of our framework and the index. Based on this, a comprehensive analyze can be conducted for the top-ranked cities instead of all potential cities. Thus, the framework can support in the decision-making process for implementing new mobility technologies, but also support city officials to assess the current state of their city.